Antibacterial Potential of Geothermal Plant Extracts from Jaboi Crater, Indonesia: A Thin Layer Chromatography-Bioautography Approach - Khairan, Khairan; Mubaraq, Farhil; Maulydia, Nur Balqis; Awang, Khalijah; Idroes, Rinaldi (Malacca Pharmaceutics, 2025)
Antimicrobial resistance (AMR) poses an urgent global health concern, prompting the need for alternative therapeutic agents. This study evaluated the antimicrobial potential of ethyl acetate extracts from five medicinal plant species (Memecylon edule, Garcinia dioica, Syzygium sp., Memecylon caeruleum, and Aporosa octandra) collected from the geothermal Jaboi Crater in Aceh, Indonesia. Phytochemical profiling was performed using thin layer chromatography (TLC), and antimicrobial activity was assessed via TLC-bioautography against Escherichia coli, Staphylococcus aureus, and Candida albicans. The results revealed the presence of phenolic and terpenoid compounds, with antibacterial activity observed only against E. coli. No inhibition was detected against S. aureus or C. albicans. The study highlights the selective antimicrobial potential of geothermal plant extracts and underscores the relevance of bioautography as a rapid screening tool. While preliminary, these findings support further investigation into geothermal flora as a source of antibacterial compounds and call for advanced studies to isolate active constituents and explore their mechanisms of action.